Đa dạng hóa sinh kế và nghèo đói ở vùng bị xâm nhập mặn của vùng Đồng bằng sông Cửu Long - Lê Thị Kim , Loan; Ngô Thị Thanh, Trúc; Dương Đăng, Khoa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study evaluates the impact of saltwater intrusion and other factors on the livelihood diversification of rural households in the Mekong Delta. The estimation results of the binomial logit model and the multinomial logit model show that saltwater intrusion has a negative impact on the ability to diversify the livelihoods of rural households, especially by reducing their ability to combine agricultural and wage employment. In addition, the chi-squared test and the propensity score matching method also display that there is an inverse relationship between livelihood diversification and poverty among households in the region through income. Therefore, local authorities should support and promote rural households’ efforts to diversify their livelihoods to improve incomes and reduce poverty in the face of the increasingly harsh impacts of saltwater intrusion.